Superoxide Anion Radicals Biosensor Based on Protein Extract from Deinococcus Radiodurans Immobilization by Glutaraldehyde Cross-Linked - Afifi, Muhammad Ridho; Iswantini, Dyah; Nurhidayat, Novik; Saprudin, Deden (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
A common enzyme for superoxide anion radicals biosensors is superoxide dismutase (SOD). Deinococcus radiodurans protein extract can replace the use of pure SOD enzymes for superoxide anion radicals biosensors. The purpose of this research is to determine the analytical performance of the superoxide anion radicals biosensor with protein extract of Deinococcus radiodurans immobilized on carboxymethylcellulose-gelatin-zeolit (CMC-G-Z) that is crosslinked by glutaraldehyde. The response surface method showed that the optimum condition for the biosensor was pH 7, protein extract concentration of 1075 µg/ml, zeolite concentration of 5 mg/ml, and glutaraldehyde concentration of 0.0042 M. Stability of the biosensor retained 67% of its sensitivity after use for 24 hours. The biosensor exhibits good analytical performance with a linear range from 0.1 – 0.8 mM, a detection limit of 77.84 µM, and a limit of quantification of 259.5 µM with a correlation coefficient of 0.9905.